«THE DISCOVERY OF THE OTHER IS AT THE SAME TIME THE DISCOVERY OF ONESELF» - A. A. Guseynov (Концепт: философия, религия, культура, 2017)
An Interview with a Famous Philosopher, Scientific Director of The Institute of Philosophy, Russian Academy of Sciences, Academician of the RAS Abdusalam Abdulkerimovich Guseinov (A.G.). Interviewed by Doctor of Philosophy, Professor M.V. Silantieva (M.S.) and Ph.D. Student Daria Liubinsky (D.L.). Exclusive interview to the Journal "Concept: Philosophy, Religion, Culture".